Building Resilient Ex-Migrant Families in Resapombo Village, Blitar - Santoso, Nobertus Ribut; Astuti, R.A. Vita N.P.; Pawana, Sekhar Candra; Negoro, Sherly Hindra; Pratama, Brahma Putra; Aryoputro, Felix Bimo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
Family relationship changes occur due to economic and social disruption. The community service aims to empower ex-migrant families in Resapombo Village, Blitar. Resilient families are characterized by strong family bonds, harmonious relationships, and effective communication patterns. Meanwhile, the ex-migrant families have experienced long separations, difficult communication, and financial problems that eventually influenced the family harmony, that included the husband, wife and children, and economic stability. Programs implemented were a family harmony workshop on communication and resilience, a school seminar at SMKN 1 Doko on sexuality and reproduction, and training for cadres. The result of the workshops was creating a cadre team of eleven people by selecting and guiding candidates to assist families in conflict resolution and support. The seminar at school was such a success that the next programs were organized in the future.